Peran Perempuan Dalam Meningkatkan Ekonomi Keluarga - Narilah A. Tuara (Jurnal Ilmiah Wahana Pendidikan, 2022)
The results showed that the role of women in the Sulamadaha sub-district, West Ternate sub-district, Ternate City, was loyal in managing the business independently, both in buying bananas, managing or preserving bananas, so that this banana trading activity was more independent, the average banana seller in Sulamadaha Village, West Ternate the city of ternate in a week the sales activities carried out by banana traders differ, ranging from 10-35 kg more per day, so what is obtained is not the same because sometimes they lose or the results are less than that. For traders, the bananas sold per day are 40 kg per day, the average income per week is Rp. 500,000 rupiah more. If viewed from these data, it can be concluded that activities to help the family economy through the banana trading business carried out by women (housewives) in the Sulamadaha Setia Village have a big impact on helping family income. the researcher reviewed that the role of women in the Sulamadaha Setia village in the family apart from acting as wives and mothers in their families, there were also women carrying out their roles as working women, as the data the researchers presented at the beginning of the change. From the results of these interviews it can be concluded that the background of the women in the Sulamadaha Setia Village taking the role as workers or traders is because of economic demands, so that by appearing as workers, it is hoped that they can help their husbands support their families in meeting their family needs. In carrying out this dual role, women in Sulamadaha Village, West Ternate District, Ternate Setia City continue to carry out their functions and duties as wives and mothers in their families